Bioassay and Pathogenicity of Wheat Seed Gall Nematode Anguina Tritici - Amin, Sulaiman N.; Taher, Ibrahim I.; Omer, Fathi A. (Science Journal of University of Zakho, 2015)
Highest infection percentage recorded in Abo-graib and wahe CVs. (83.3%) followed by Smeto (80.3%) while less infection percentage was in Rezgare and Al-Aez CVs. (33.3%). more galls (14 galls/ spike) formed in Sham-2 C.V. followed by Abo-graib, Smeto, Tammoz-2, Maxipak and Al-Aez respectively. highest number of nematode (12773) occurred in large galls, while the lowest (8145) in small galls. A. tritici population density increased dramatically with increase in galls size reached a peak (15112 second stage juveniles/gall) in big size gall. Results revealed that the vitality of second stage juveniles reached its maximum level (8.87%) at 12 Cº with no significant differences with the validity percentage at 6 Cº while it reached its minimum level (1%) at 20 Cº.